Population aging, elderly migration and education spending: intergenerational conflict revisited - Mehmet Serkan Tosun; Claudia R. Williamson; Pavel Yakovlev (Institute for the Study of Labor (IZA), 2009)
Elderly have been increasingly targeted as a group to enhance economic development and the tax base in communities. While recent literature on elderly migration tends to focus on how elderly migration patterns are influenced by state fiscal variables, the reverse effect from elderly population on fiscal variables is very plausible. This paper reexamines the intergenerational conflict in education financing using U.S. state and county level data. We analyze how preferences for education spending might vary across different elderly age groups, an analysis that has not been explored before. We estimate the impact of elderly population and elderly migration rates on education spending using panel data and spatial econometric techniques. Our results broadly support the presence of intergenerational conflict and age heterogeneity in preferences for education spending among elderly migrants.
urn:nbn:de:101:1-20090605181
Keywords: H75; R23; 330; Population aging; elderly migration; education spending; intergenerational conflict; Bildungsfinanzierung; Öffentliche Bildungsausgaben; Altersgruppe; Generationenbeziehungen; Internationale Wanderung; Alternde Bevölkerung; USA